Upper ordovician (Sandbian) bryozoan fauna from argentine precordillera - Ernst, Andrej (2012)
A stenolaemate bryozoan fauna containing 20 species belonging to 18 genera is described from the Las Plantas and Las Aguaditas formations (Upper Ordovician, Sandbian) in San Juan Province, Precordillera of Western Argentina. One genus with one species is new: Argentinodictya lenticulata n. gen. n. sp. (Cryptostomata, Ptilodictyina). Four species are new: one trepostome Parvohallopora parvula n. sp., two cryptostomes Trigonodictya parvula n. sp. and Ptilodictya intermedia n. sp., and phyloporinine Chasmatopora rossae n. sp. The bryozoan assemblage of the Las Plantas Formation is more diverse than that of the Las Aguaditas Formation. Fourteen species are restricted to the Las Plantas Formation, five species occur in both formations, and one species is restricted to the Las Aguaditas Formation. Erect growth forms are dominant in the studied fauna. The majority of bryozoan taxa display palaeobiogeographic relations to SandbianKatian deposits of North America, with two species also known from the Katian of Europe.